Molecular Characterization of the 1-Deoxy-D-Xylulose 5-Phosphate Synthase Gene Family in Artemisia annua - Zhang, Fangyuan; Liu, Wanhong; Xia, Jing; Zeng, Junlan; Xiang, Lien; Zhu, Shunqin; Zheng, Qiumin; Xie, He; Yang, Chunxian; Chen, Min; Liao, Zhihua (Frontiers in Plant Science, 2018)
Artemisia annua produces artemisinin, an effective antimalarial drug. In recent decades, the later steps of artemisinin biosynthesis have been thoroughly investigated; however, little is known about the early steps of artemisinin biosynthesis. Comparative transcriptomics of glandular and filamentous trichomes and 13CO2 radioisotope study have shown that the 2-C-methyl-D-erythritol-4-phosphate (MEP) pathway, rather than the mevalonate (MVA) pathway, plays an important role in artemisinin biosynthesis. In this study, we cloned three 1-deoxy-D-xylulose 5-phosphate synthase (DXS) genes from A. annua (AaDXS1, AaDXS2, and AaDXS3); the DXS enzyme catalyzes the first and rate-limiting enzyme of the MEP pathway. We analyzed the expression of these three genes in different tissues and in response to multiple treatments. Phylogenetic analysis revealed that each of the three DXS genes belonged to a distinct clade. Subcellular localization analysis indicated that all three AaDXS proteins are targeted to chloroplasts, which is consistent with the presence of plastid transit peptides in their N-terminal regions. Expression analyses revealed that the expression pattern of AaDXS2 in specific tissues and in response to different treatments, including methyl jasmonate, light, and low temperature, was similar to that of artemisinin biosynthesis genes. To further investigate the tissue-specific expression pattern of AaDXS2, the promoter of AaDXS2 was cloned upstream of the -glucuronidase (GUS) gene and introduced in Arabidopsis. Histochemical staining assays demonstrated that AaDXS2 was mainly expressed in the trichomes of Arabidopsis leaves. Together, these results suggest that AaDXS2 might be the only member of the DXS family in A. annua that is involved in artemisinin biosynthesis.